Analysis of the Trigeminal Comb Traits in White-ear Yellow Chicken - Wenwu ZHANG; Fengfang QIU; Jiguo XU (Guangdong nongye kexue, 2022)
【Objective】The study was carried out to find candidate single nucleotide polymorphisms (SNP) loci associated with the trigeminal comb traits in white-ear yellow chickens.【Method】Sixty white-ear yellow chickens were used for crossbreeding experiment and 120 white-ear yellow chickens were used for fertility rate experiment. The blood samples of eighty-two white-ear yellow chickens were collected for DNA extraction, and then genotype classification was conducted by using Illumina chicken 60 k microarrays. After using PLINK 1.90 for quality control of the genotyping results, GEMMA software was used to perform genome-wide association analysis (GWAS) on SNP and traits to find SNP loci significantly associated with trigeminal comb traits in white-ear yellow chickens.【Result】The trigeminal comb of white-ear yellow chicken showed autosomal inheritance and the egg fertility rate was not significantly different from that of the white-ear yellow chicken with single comb. 55 023 valid SNPs were obtained from the population of 82 white-ear yellow chickens and there was no significant population stratification within the population. Ten SNP loci associated with trigeminal comb were located on chromosomes 1, 2, 3, 4, 5, 12 and 14 of white-ear yellow chickens, adjacent to or located on SPRY2, NDFIP2, ITGA9, EMC2, TMEM17, EHBP1, SCAF8, TIAM2, HTT, STON2, PRKCD, RBBP6, TNRC6A and MAPK8IP3 genes.【Conclusion】Based on the GWAS analysis, it is found that 10 SNPs loci may be associated with the trigeminal comb traits in white-ear yellow chickens. These results will provide candidate molecular markers for the breeding of white-ear yellow chickens and new ideas for marker-assisted selection of local chickens.